2018
DOI: 10.1155/2018/6518572
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Noninvasive Helmet Ventilation Compared with Use of Noninvasive Face Mask in ARDS

Abstract: Intensive care unit (ICU) costs have doubled since 2000, totalling 108 billion dollars per year. Acute respiratory distress syndrome (ARDS) has a prevalence of 10.4% and a 28-day mortality of 34.8%. Noninvasive ventilation (NIV) is used in up to 30% of cases. A recent randomized controlled trial by Patel et al. (2016) showed lower intubation rates and 90-day mortality when comparing helmet to face mask NIV in ARDS. The population in the Patel et al. trial was used for cost analysis in this study. Projections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The cost of each hood is measured in hundreds of dollars as opposed to the thousands of dollars range when compared with mechanical ventilation. Furthermore, this therapy decreases overall hospital costs associated with the prolonged ICU admission mechanical ventilation entails [ 17 ]. While the rubberneck gaskets are used for single patients due to the customized sizing procedure required, the hoods can be sterilized and reused on multiple patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of each hood is measured in hundreds of dollars as opposed to the thousands of dollars range when compared with mechanical ventilation. Furthermore, this therapy decreases overall hospital costs associated with the prolonged ICU admission mechanical ventilation entails [ 17 ]. While the rubberneck gaskets are used for single patients due to the customized sizing procedure required, the hoods can be sterilized and reused on multiple patients.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of helmets is even more remarkable considering that the ventilator setting with the helmet was not optimized according to the principles described above and the likelihood that some CO 2 rebreathing occurred. Moreover, helmet use could also be cost-effective [ 73 , 74 ]. Helmet NPPV might also be used as an alternative to invasive ventilation during the weaning phase, with a similar ventilatory support duration but fewer infectious complications [ 75 ].…”
Section: Use Of Helmets To Deliver Nppvmentioning
confidence: 99%
“…It may be related to the fact that most of the primary causes of hypoxemic ARF are reversible, while most of the primary diseases leading to hypercapnic ARF are irreversible. In addition, some researchers conducted economic analysis [49] showed that the cost of ICU and hospitalization of the helmet NIMV group was significantly lower than that of the face mask NIMV group, reflecting considerable economic advantage.…”
Section: Plos Onementioning
confidence: 99%